Anxiety and Coping Stress Strategies in Researchers During COVID-19 Pandemic - Batista, Patrícia; Afonso, Anabela; Lopes, Manuel; Fonseca, César; Oliveira-Silva, Patrícia; Pereira, Anabela; Pinho, Lara (Frontiers in Public Health, 2022)
The current COVID-19 pandemic has affected the whole world, leading to changes in one's personal and working life. Researchers have undergone extensive changes in their roles, mainly in the area of health care, with research into the virus now the priority. Aim To assess the anxiety, depression, stress, fears, and coping strategies of Portuguese researchers during the COVID-19 pandemic. Participants and Methods A total of 243 researchers, with an average age of 37.9 ± 9.6, participated in an online questionnaire. The study was performed between 1 June 2021 and 11 August 2021. The questionnaire included depression, anxiety, and stress (DASS-21), fear of COVID-19 scale (FCV-19S), and coping inventory for stressful situations (CISS). Results The findings suggest being female and younger seem to be related to more significant fears. Singles and younger researchers showed higher values of stress, depression, and anxiety. Research areas, such as medical and health sciences, presented higher levels in the DASS-21 depression and stress scale (p < 0.05). Also, the results showed a moderate or moderate strong significant positive linear relationship between the scales (p < 0.001): DASS-21 stress, DASS-21 anxiety, and DASS-21 depression (r > 0.70); CISS-21 emotional-oriented with DASS-21 stress (r = 0.683), DASS-21 depression (r = 0.622), and DASS-21 anxiety (r = 0.557); and emotional fear and cognitive fear (r = 0.652). Conclusion The findings of this study support the growing concern for the psychological well-being of researchers and the need for intervention with more extensive and diverse studies.